Pain Management Intervention in Overcoming Dysmenorrhea in Adolescent Girls at the Bina Dakwah Islamic Boarding School, Loa Bakung District Samarinda - Adiasih, Nisa Solikha; Safrudin, Muhammad Bachtiar (Poltekkes Kemenkes Aceh, 2024)
Background: The setting of community health services in at-risk groups is often not optimal due to the distance of access to available health services, the lack of promotive efforts of health facilities in providing disease prevention education so that this will have an impact on community health deficiencies in adolescents and ineffective health maintenance. In order for the prevalence of dysmenorrhea problems in the community setting to be reduced, preventive management is needed, namely by reducing community health problems by carrying out several community health programs such as maintaining the management of pain problems as a result of dysmenorrhea symptoms. Purpose: To determine the level of knowledge and pain of dysmenorrhea in adolescents at the Bina Dakwah Islamic Boarding School, Loa Bakung District, Samarinda after pain management was carried out. Methods: Descriptive research type through nursing process approach involving 5 respondents. The research instrument used Visual Analog Scale (VAS) to measure the pain scale and knowledge level questionnaire related to adolescent dysmenorrhea pain. Results: Management of dysmenorrhea pain in adolescents through education, dysmenorrhea exercises, and reflexology massage resulted in an increase in the average pain score from 8.2 to 11.8. Meanwhile, for dysmenorrhea pain, there was a decrease on the 3rd day, namely from mild pain (scale 3 to 4) to no pain. Conclusion: Providing dysmenorrhea management through education, dysmenorrhea exercises, and reflexology massage can increase knowledge and reduce pain in adolescents at the Bina Dakwah Islamic Boarding School, Loa Bakung District, Samarinda.